Synergistic Action of Ampicillin and Erythromycin Against Nocardia asteroides: Effect of Time of Incubation - Finland, Maxwell (1974)
Ampicillin and erythromycin were shown to act synergistically in vitro against the majority of strains of Nocardia asteroides tested. With these strains, the minimal inhibiting concentration (MIC) of each drug when combined was reduced 4- to more than 512-fold as compared with the MIC of each antibiotic acting individually against the same strains. The combined action against other strains was at least additive, and occasionally indifferent, but antagonism was not observed. The duration of incubation greatly influenced the MIC of erythromycin but had less effect on the action of ampicillin. Synergistic action was still demonstrable, although less frequently, when the period of incubation was increased from 48 to 72 h.